The Established Nuclear Medicine Modalities for Imaging of Bone Metastases - Jabeen, Nazish; Rasheed, Rashid; Rafique, Asma; Murtaza, Ghulam (Current Medical Imaging, 2019)
Background: The skeleton is one of the frequent site of metastases in advanced cancer. Prostate, breast and renal cancers mostly metastasize to bone. Discussion: Malignant tumors lead to significant morbidity and mortality. Identification of bone lesions is a crucial step in diagnosis of disease at early stage, monitoring of disease progression and evaluation of therapy. Diagnosis of cancer metastases is based on uptake of bone-targeted radioactive tracer at different bone remodeling sites. Conclusion: This manuscript summarizes already established and evolving nuclear medicine modalities (e.g. bone scan, SPECT, SPECT/CT, PET, PET/CT) for imaging of bone metastases.
Keywords: diagnosis